Self-esteem and health indicators in Polish postmenopausal women - Krupa-Kotara, Karolina; Gdańska, Agnieszka; Grajek, Mateusz; Günay, Tuğrul; Rozmiarek, Mateusz (Frontiers in Nutrition, 2025)
BackgroundAging populations face health and psychosocial challenges that can affect their quality of life. This study aimed to examine the relationship between self-esteem and selected health indicators among older women in Poland.MethodsSix hundred women aged 60+ attending Third Age Universities were surveyed. BMI, waist-to-hip ratio (WHR), daily physical activity (steps), fasting glucose and cholesterol levels, and self-esteem (Rosenberg Self-Esteem Scale) were assessed.ResultsAdverse health indicators such as high BMI, WHR, and elevated glucose were associated with lower self-esteem (p < 0.05). Cholesterol levels showed no significant relationship.ConclusionThese findings suggest that maintaining a healthy lifestyle and metabolic balance may contribute to better psychological wellbeing for older women. Community-based physical activity initiatives may support psychological wellbeing among postmenopausal women.